Kedudukan Penyandang Disabilitas dalam Melakukan Pembuatan Perjanjian Pasca Judicial Review Pasal 433 KUHPerdata - Rafid Algiffari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study discusses the position of persons with disabilities, especially those with mental and intellectual disabilities, in carrying out legal actions following the judicial review of Article 433 of the Civil Code through the Constitutional Court Decision Number 93/PUU-XX/2022. Prior to this amendment, Article 433 of the Civil Code used discriminatory terms and automatically placed persons with disabilities under guardianship, thereby eliminating their legal capacity as independent legal subjects. This Constitutional Court decision changed the phrase